The effectiveness of positive thinking training on perceived stress and happiness in patients with thalassemia major - Ommolbanin Roodbari; Hossein Zare; Hadis Saeedi; Kouros Divsalar; Fatemeh Eslamian (Islamic Azad University, 2015)
Introduction: Thalassemia disease is a hereditary chronic hemolytic anemia. Since in chronic diseases complete and perfect healing is out of reach, by the support of psychology we can help these patients to accept that they can change their views and enjoy from their abilities. In addition, this disease cannot ruin their cheerfulness and their family lives. Methods: This semi-experimental type of research had a pre-test, post-test design with a control group. The study sample included 20 girls who are inflicted with thalassemia major. Based on available sampling they were randomly assigned into two groups of 10 (experiment and control) respectively. Positive thinking sessions were held twice a week for 10 sessions with a duration of 60 minutes. In order to gather data, the Perceived Stress Scale (PSS) and Oxford happiness questionnaire were used. Data were analyzed using covariance analysis method. SPSS software version 18 was used for data analysis. Results: Findings showed that positive thinking sessions decreased perceived stress but had an increasing effect on happiness for those with thalassemia major. Conclusion: Thus, holding positive thinking workshops for these patients is recommended.